SOCIAL INTELLIGENCE AND ACHIEVEMENT IN SCIENCE AMONG HIGHER SECONDARY SCHOOL STUDENTS - D.Vinodhkumar; Pankajam, R. (International Journal of Research -GRANTHAALAYAH, 2017)
The present study intended to find out the level of Social Intelligence and Achievement in Science among Higher Secondary School Students. This study belongs to Survey Method. The size of the sample in the study was 300 Higher Secondary School Students who were selected through Random Sampling Technique. The investigators had used Social Intelligence Scale developed by Baskaran. P and Anandan. K (2011) and Achievement Test in Science (ATS) developed by the Investigators. The Statistical techniques used in this study were Mean, Standard deviation, t’ test and Correlation to analyse the data. It was inferred that there is significant relationship between Social Intelligence and Achievement in science among selected High School Students.